Analyses of volatile organic compounds from human skin - Gallagher, M.; Wysocki, C.J.; Leyden, J.J.; Spielman, A.I.; Sun, X.; Preti, G. (British journal of dermatology (1951), 2008)
Summary Background  Human skin emits a variety of volatile metabolites, many of them odorous. Much previous work has focused upon chemical structure and biogenesis of metabolites produced in the axillae (underarms), which are a primary source of human body odour. Nonaxillary skin also harbours volatile metabolites, possibly with different biological origins than axillary odorants. Objectives  To take inventory of the volatile organic compounds (VOCs) from the upper back and forearm skin, and assess their relative quantitative variation across 25 healthy subjects. Methods  Two complementary sampling techniques were used to obtain comprehensive VOC profiles, viz., solid‐phase microextraction and solvent extraction. Analyses were performed using both gas chromatography/mass spectrometry and gas chromatography with flame photometric detection. Results  Nearly 100 compounds were identified, some of which varied with age. The VOC profiles of the upper back and forearm within a subject were, for the most part, similar, although there were notable differences. Conclusions  The natural variation in nonaxillary skin odorants described in this study provides a baseline of compounds we have identified from both endogenous and exogenous sources. Although complex, the profiles of volatile constituents suggest that the two body locations share a considerable number of compounds, but both quantitative and qualitative differences are present. In addition, quantitative changes due to ageing are also present. These data may provide future investigators of skin VOCs with a baseline against which any abnormalities can be viewed in searching for biomarkers of skin diseases.